Performance of broilers fed diets containing natural growth promoters - Pelicano, ERL [UNESP] (2004)
The present study evaluated the effect of different probiotics on the performance of broiler chickens. A thousand and fifty one-day-old male Cobb chicks were distributed in a completely randomized design in a 3 x 2 + 1 factorial arrangement (3 probiotics sources in the diet, 2 probiotics concentrations in drinking water and 1 control group), with 5 repetitions of 30 birds per parcel. The results showed better feed conversion (p<0.01) (1-21, 22-35 and 1-45 days) and weight gain (p<0.05) (22-35 and 1-45 days) in the control group in relation to the groups receiving probiotics. The use of Bacillus subtilis in the diet improved (p<0.05) feed conversion during the growing phase, but this was not seen in the following period. Thus, it was concluded that probiotics supplementation had no beneficial effects on the performance.